Răspuns :
[tex]2 \times 25^{x} - 5^{x+1} = 25[/tex]
[tex]2 \times ( {5}^{2} )^{x} - 5^{x} \times 5^{1} = 25[/tex]
[tex]2 \times ({5}^{x} )^{2} - {5}^{x } \times 5^{1} = 25[/tex]
Notăm
[tex] {5}^{x} [/tex]
cu o necunoscută t
[tex]2 \times t ^{2} - t \times 5 = 25[/tex]
[tex]2 {t}^{2} - 5t - 25 = 0[/tex]
Deci ecuație de grad 2:
[tex]a = 2 \\ b = - 5 \\ c = - 25[/tex]
delta =
[tex] {b}^{2} - 4 \times a \times c \\ = 25 - ( - 200) \\ = 225[/tex]
[tex]x1 = \frac{5 - \sqrt{225} }{2 \times 2 } \\ x1 = \frac{5 - 15}{4} \\ x1 = - \frac{10}{4} \\ x1 = - \frac{5}{2} [/tex]
ceea ce nu se poate.
[tex]x2 = \frac{5 + \sqrt{225} }{2 \times 2} \\ x2 = \frac{5 + 15}{4} \\ x2 = \frac{20}{4} \\ x2 = 5[/tex]
ceea ce rezultă că:
[tex]t = 5 \\ {5}^{x} = {5} \\ {5}^{x} = {5}^{1} \\ \\ x = 1[/tex]